Tunable Carrier Transfer of Polymeric Carbon Nitride with Charge-Conducting CoV2O6∙2H2O for Photocatalytic O2 Evolution - Shaohong Zang; Xiaorong Cai; Mengshan Chen; Dehong Teng; Fei Jing; Zhe Leng; Yingtang Zhou; Feng Lin (Nanomaterials, 2022)
Photocatalytic water splitting is one of the promising approaches to solving environmental problems and energy crises. However, the sluggish 4e− transfer kinetics in water oxidation half-reaction restricts the 2e− reduction efficiency in photocatalytic water splitting. Herein, cobalt vanadate-decorated polymeric carbon nitride (named CoVO/PCN) was constructed to mediate the carrier kinetic process in a photocatalytic water oxidation reaction (WOR). The photocatalysts were well-characterized by various physicochemical techniques such as XRD, FT-IR, TEM, and XPS. Under UV and visible light irradiation, the O2 evolution rate of optimized 3 wt% CoVO/PCN reached 467 and 200 μmol h−1 g−1, which were about 6.5 and 5.9 times higher than that of PCN, respectively. Electrochemical tests and PL results reveal that the recombination of photogenerated carriers on PCN is effectively suppressed and the kinetics of WOR is significantly enhanced after CoVO introduction. This work highlights key features of the tuning carrier kinetics of PCN using charge-conducting materials, which should be the basis for the further development of photocatalytic O2 reactions.